Achieving Employability as We Age: The Role of Age and Achievement Goal Orientations on Learning and Employability - Dominik E. Froehlich; Sandra Aasma; Simon Beausaert (Administrative Sciences, 2020)
The aging workforce challenges companies to keep their aging employees employable in the workforce. This paper gives an indication as to which employees are more likely to be interested in further learning and employability. Specifically, the aim of this study was to investigate the role of chronological age and achievement goal orientations for informal and formal learning and employability. Data of 167 Austrian knowledge workers were gathered via electronic questionnaires to investigate the relationships between age, achievement goal orientations, learning activities, and employability using structural equation modeling. It was found that informal learning has a significant positive relation with several dimensions of employability. Furthermore, mastery-approach goal orientation also shows a significant positive relation with informal learning and employability. In addition, age had no significant relation with the achievement goal orientations. The paper stresses the need to consider characteristics other than chronological age, such as goal orientations, when considering employees’ learning behavior and employability.